Maps and diagrams : - Monkhouse, F. J. (Methuen, 1971)
This book seeks, in the limited additional space available, to give students some idea of the novel and exciting developments in tools, materials, techniques and methods (notably in the realms of quantification, machanization and automation), with on the one hand immeasurably speed up the production of maps, and on the other hand enable them to be based om vast masses of information which could hardly be dealt with manually